Behavioral and transcriptomic profiling of mice null for Lphn3, a gene implicated in ADHD and addiction. Issue 3 (4th March 2016) - Orsini, Caitlin A.; Setlow, Barry; DeJesus, Michael; Galaviz, Stacy; Loesch, Kimberly; Ioerger, Thomas; Wallis, Deeann
Abstract: Background: The Latrophilin 3 ( LPHN3 ) gene (recently renamed Adhesion G protein‐coupled receptor L3 (ADGRL3 )) has been linked to susceptibility to attention deficit/hyperactivity disorder (ADHD) and vulnerability to addiction. However, its role and function are not well understood as there are no known functional variants. Methods: To characterize the function of this little known gene, we phenotyped Lphn3 null mice. We assessed motivation for food reward and working memory via instrumental responding tasks, motor coordination via rotarod, and depressive‐like behavior via forced swim. We also measured neurite outgrowth of primary hippocampal and cortical neuron cultures. Standard blood chemistries and blood counts were performed. Finally, we also evaluated the transcriptome in several brain regions. Results: Behaviorally, loss of Lphn3 increases both reward motivation and activity levels. Lphn3 null mice display significantly greater instrumental responding for food than wild‐type mice, particularly under high response ratios, and swim incessantly during a forced swim assay. However, loss of Lphn3 does not interfere with working memory or motor coordination. Primary hippocampal and cortical neuron cultures demonstrate that null neurons display comparatively enhanced neurite outgrowth after 2 and 3 days in vitro. Standard blood chemistry panels reveal that nulls have low serum calcium levels. Finally, analysis of the transcriptome from prefrontal cortical, striatal, and hippocampal tissue at different developmental time points shows that loss of Lphn3 results in genotype‐dependent differential gene expression (DGE), particularly for cell adhesion molecules and calcium signaling proteins. Much of the DGE is attenuated with age, and is consistent with the idea that ADHD is associated with delayed cortical maturation. Conclusions: Transcriptome changes likely affect neuron structure and function, leading to behavioral anomalies consistent with both ADHD and addiction phenotypes. The data should further motivate analyses of Lphn3 function in the developmental timing of altered gene expression and calcium signaling, and their effects on neuronal structure/function during development. Abstract : LPHN3 has been associated with both ADHD and vulnerability to addiction. We evaluated a Lphn3 null mouse and observed changes in behavior that encompass both activity levels and reward motivation. We also observe altered serum calcium levels; neurite outgrowth; and neurotransmitter levels. Further, our data indicate that loss of Lphn3 leads to developmentally dynamic alterations in the transcriptome and suggest that cell adhesion molecules and calcium‐dependent signaling proteins are affected. These transcriptomic and neuronal changes in structure and function are anticipated to affect the brain as a whole and further result in changes in behavior.